2022
DOI: 10.3390/biomedicines10020234
|View full text |Cite
|
Sign up to set email alerts
|

Decreased SLC27A5 Suppresses Lipid Synthesis and Tyrosine Metabolism to Activate the Cell Cycle in Hepatocellular Carcinoma

Abstract: Tyrosine is an essential ketogenic and glycogenic amino acid for the human body, which means that tyrosine is not only involved in protein metabolism, but also participates in the metabolism of lipids and carbohydrates. The liver is an important place for metabolism of lipids, carbohydrates, and proteins. The metabolic process of biological macro-molecules is a basis for maintaining the physiological activities of organisms, but the cross-linking mechanism of these processes is still unclear. Here, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The tyrosine metabolic pathway is a crucial part of biological processes that is involved in making neurotransmitters, hormones, and melanin. Previous studies have shown that the end products of this metabolic pathway are involved in lipid biosynthesis, implying crosstalk between metabolite-mediated tyrosine and lipid metabolism ( Wang J. et al, 2022 ). The results suggest that the pathogenic changes occurring in the formative stage of HCC in mice predominantly included lipid metabolism, amino acid metabolism, and glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tyrosine metabolic pathway is a crucial part of biological processes that is involved in making neurotransmitters, hormones, and melanin. Previous studies have shown that the end products of this metabolic pathway are involved in lipid biosynthesis, implying crosstalk between metabolite-mediated tyrosine and lipid metabolism ( Wang J. et al, 2022 ). The results suggest that the pathogenic changes occurring in the formative stage of HCC in mice predominantly included lipid metabolism, amino acid metabolism, and glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, tyrosine is produced by the conversion of phenylalanine through phenylalanine, tyrosine and tryptophan biosynthesis. Previous research has demonstrated a substantial association between the malfunction of tyrosine metabolic pathways and liver cancer ( Wang J. et al, 2022 ). Fumaric acid and acetoacetate, which are the end products of tyrosine metabolism, can be converted to acetyl-CoA, which is involved in lipid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…We know that not only the cell cycle [45], but also metabolic pathways, play a role in the progression of hepatocellular carcinoma [46,47]. For example, reduced tyrosine metabolism activates the cell cycle and promotes cell proliferation [48], and enzymes involved in glycolysis, such as Pyruvate kinase-Pyruvate kinase M2 (PKM2), are highly expressed and are strongly related to a bad OS in HCC [46]. Besides, the LinkOmics dataset identified the key roles of ARHGAP39 in the cell cycle, hippo signaling pathway, spliceosome, and RNA transport.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HPD is also a prognostic predictor and a potential therapeutic target in breast cancer 34 . Surprisingly, tyrosine metabolism was significantly downregulated in liver and kidney cancers, which in turn activated the cell cycle and promoted tumor progression 35,36 . The refractory glioma is largely due to the heterogeneity of the tumor, so identifying the subtype of glioma has guiding significance for its clinical treatment.…”
Section: Discussionmentioning
confidence: 99%